The Confluence of Karma and Hygiene Vegetarianism with Renewed Meanings for Modern Chinese Buddhism - Lu, Lianghao (2021)
This article provides a comprehensive account of the transformation of Buddhist vegetarian discourse in the Republican era (1912-1949) through the lens of a set of Buddhist periodicals influenced by prominent figures, including Taixu 太虛 (1890-1947), Yinguang 印光 (1862-1940), and Dixian 諦閒 (1858-1932). Having combed through relevant articles printed in these journals, I argue that Buddhist vegetarianism is infused with modern scientific language, particularly the Western biomedical concept of “hygiene,” while it also retains the underlying reasoning of karmic retribution and Buddhist ethical arguments. Within a modern context, these authors proffered different yet not antagonistic reasoning to renew and legitimate the practice of vegetarianism. I further examine the case of Lü Bicheng 呂碧城 (1883-1943) to demonstrate the potential fusion of diverse rationales regarding the vegetarian discourse under the broader international social and cultural order. Thus, the Republican Buddhists’ endeavors resulted in a repertoire of rhetoric and arguments about vegetarianism, imbuing the practice with multilayered meanings ready for appropriation by later generations.
Keywords: Buddhist modernization; Buddhist periodicals; Republican-era Buddhism; 佛教期刊; 佛教現代化; 民國佛教; 素食主義; 衛生; Hygiene; Vegetarianism